2016
DOI: 10.1038/srep24825
|View full text |Cite
|
Sign up to set email alerts
|

The effects of salinity on nitrification using halophilic nitrifiers in a Sequencing Batch Reactor treating hypersaline wastewater

Abstract: With annual increases in the generation and use of saline wastewater, the need to avoid environmental problems such as eutrophication is critical. A previous study identified ways to start up a halophilic sludge domesticated from estuarine sediments to remove nitrogen from wastewater with a salinity of 30 g/L. This investigation expands that work to explore the impact of salinity on nitrogen removal. This study demonstrated that the mixed halophilic consortia removed nitrogen from wastewater with a salinity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 29 publications
1
26
1
1
Order By: Relevance
“…The same study also found that relative enzyme activities of lipase and nitrate reductase increased by 32% and 35%, respectively, in the presence of 1 mmol L −1 ectoine. 18 Liu et al 16 found that 1 mmol L −1 glycine betaine was most effective in alleviating salt toxicity in anammox biomass. It is likely that different compatible solutes have different mechanisms and different optimum addition on AnAOB and HDB.…”
Section: Long-term Effect Resulting From Mannitol Addition On Sad Promentioning
confidence: 99%
See 2 more Smart Citations
“…The same study also found that relative enzyme activities of lipase and nitrate reductase increased by 32% and 35%, respectively, in the presence of 1 mmol L −1 ectoine. 18 Liu et al 16 found that 1 mmol L −1 glycine betaine was most effective in alleviating salt toxicity in anammox biomass. It is likely that different compatible solutes have different mechanisms and different optimum addition on AnAOB and HDB.…”
Section: Long-term Effect Resulting From Mannitol Addition On Sad Promentioning
confidence: 99%
“…However, acclimatization time may be quite long and microbial salt resistance can be easily lost if the salt concentration selection pressure is removed . Although microorganisms are able to survive in high salinity environments through bio‐augmentation with halophilic species to achieve more stable and durable process performance, it is not easy to maintain dominance of such species in mixed culture systems …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrification in soils is a central component of N biogeochemical cycling and involves the oxidation of ammonia + (NH ) 4 to nitrite − (NO ) 2 , along with further oxidation to nitrate − (NO ) 3 . The process has significant environmental and agricultural impacts on N nutrient availability for plants, NO 3 − N leaching, and greenhouse gases emissions [1][2][3] . Specifically, ammonia oxidation and nitrite oxidation are the two key steps of nitrification.…”
mentioning
confidence: 99%
“…In addition, high salt content induces cell lysis, which causes increased effluent solids. The populations of protozoa and filamentous organisms required for proper flocculation were also significantly reduced by the elevated salt content [13][14][15][16][17] . Therefore, high salinity in fish processing wastewater will lead to difficulties in biological treatment processes 13 .…”
Section: Effect Of Salt Concentration To Efficiencymentioning
confidence: 99%